Bilateral Arteriovenous Shunts as a Method for Evaluating Tissue-Engineered Vascular Grafts in Large Animal Models(*) - Ong, Chin Siang (Tissue Eng Part C Methods, 2017)
There remains a need for large animal models to evaluate tissue-engineered vascular grafts (TEVGs) under arterial pressure to provide preclinical data for future potential human clinical trials. We present a comprehensive method for the interrogation of TEVGs, using an ovine bilateral arteriovenous (AV) shunt implantation model. Our results demonstrate that this method can be performed safely without complications, specifically acute heart failure, steal syndrome, and hypoxic brain injury, and it is a viable experimental paradigm. Our method allows for a non-invasive evaluation of TEVGs in terms of graft flow, graft diameter, and graft patency, while also allowing for graft needle puncture under ultrasound guidance. In addition, traditional pathological analysis, histology, and immunohistochemistry may be performed with the contralateral side providing paired control data to eliminate inter-subject variability while reducing the total number of animals. Further, we present a review of existing literature of preclinical evaluation of TEVGs in large animal models as AV conduits.